2021
DOI: 10.1002/cam4.4207
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia on preoperative chest computed tomography predicts cancer‐specific and all‐cause mortality following pneumonectomy for lung cancer: A multicenter analysis

Abstract: Background Mortality risk prediction in patients undergoing pneumonectomy for non‐small cell lung cancer (NSCLC) remains imperfect. Here, we aimed to assess whether sarcopenia on routine chest computed tomography (CT) independently predicts worse cancer‐specific (CSS) and overall survival (OS) following pneumonectomy for NSCLC. Methods We included consecutive adults undergoing standard or carinal pneumonectomy for NSCLC at Massachusetts General Hospital and Heidelberg University from 2010 to 2018. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The muscle index on the different thoracic vertebral levels exhibited different predictive capacities for survival, due in part to the fact that pectoralis muscles at T4 support upper extremity and respiratory system function (40). However, there are some limitations in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The muscle index on the different thoracic vertebral levels exhibited different predictive capacities for survival, due in part to the fact that pectoralis muscles at T4 support upper extremity and respiratory system function (40). However, there are some limitations in this study.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, one study found that patients with progressive disease had significantly lower SMI/T11 levels compared with stable disease in lung cancer (39). Similarly, another study reported that muscle mass at T8 level (not T10 level) was the best predictor of survival, and muscle mass at T12 showed no association with survival in lung cancer (40). In line with prior studies, our results revealed that PMI/T4 may be more helpful in survival prediction than SMI/T11 in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Body composition measures for the current study were acquired from CT images that were obtained as part of pretreatment clinical evaluation, a strategy that has been successfully used in other populations. 32 To date, studies that have linked these CT-based measurements to outcomes after cancer treatment have largely been in patients with solid malignancies, [9][10][11][12]33 including those with gastrointestinal cancers, because of the association between nutritional deficiencies and availability of abdominal imaging. We recently reported on the association between pretreatment skeletal muscle health and increased risk of acute toxicities in patients undergoing HCT for hematologic malignancies, including a higher risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal skeletal muscle measurements at baseline such as low muscle mass and resultant fat infiltration (myosteatosis) have been associated with adverse cancerrelated outcomes and all-cause mortality in patients with solid and hematologic malignancies, [9][10][11][12] including in those undergoing hematopoietic cell transplantation (HCT). [13][14][15] For patients undergoing CAR T-cell therapy, abnormally low skeletal muscle prior to CAR T-cell infusion may be of particular clinical relevance, given the increasing recognition of the role of muscle as a regulator of immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of visceral and subcutaneous abdominal adipose tissue as a risk factor for cardiovascular events and a metabolic marker in cancer has been quantified together with hepatic steatosis [ 3 , 39 , 40 , 41 ]. Previous approaches have performed automated segmentation of abdominal body composition based on thresholding and region growing, in conjunction with probabilistic filtering of intensities and with active contours to increase robustness [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%